2021
DOI: 10.3390/polym13060859
|View full text |Cite
|
Sign up to set email alerts
|

Spatially Controlled Highly Branched Vinylsilicones

Abstract: Branched silicones possess interesting properties as oils, including their viscoelastic behavior, or as precursors to controlled networks. However, highly branched silicone polymers are difficult to form reliably using a “grafting to” strategy because functional groups may be bunched together preventing complete conversion for steric reasons. We report the synthesis of vinyl-functional highly branched silicone polymers based, at their core, on the ability to spatially locate functional vinyl groups along a sil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…It is relatively straightforward to convert a single vinyl group on a silicone polymer—a class of compounds readily available in monofunctional, telechelic (α,ω-substituted), random pendent and precise pendent formats—into a trivinylsilicone [ 29 ]. To do so, two iterative steps are used to get to the next generation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is relatively straightforward to convert a single vinyl group on a silicone polymer—a class of compounds readily available in monofunctional, telechelic (α,ω-substituted), random pendent and precise pendent formats—into a trivinylsilicone [ 29 ]. To do so, two iterative steps are used to get to the next generation.…”
Section: Resultsmentioning
confidence: 99%
“…Silicones are very sensitive to acids/bases, which makes routes to precise silicones, such as dendrons, normally difficult. However, the Piers-Rubinsztajn (PR) reaction [ 28 ] is particularly conducive to the preparation of highly branched silicones with spatial control [ 29 ], including dendrimers [ 30 , 31 ] ( Figure 1 c).…”
Section: Introductionmentioning
confidence: 99%
“…The P-R reaction provides a high level of structural control that is needed for the synthesis of various siloxane copolymers with regularly distributed functional groups or blocks. Linear poly(dimethylsiloxane-co-vinylmethyldisiloxane) with the controlled spacing of vinyl functional groups was obtained in the P-R reaction of dimethoxymethylvinylsilane with linear polydimethylsiloxanes terminated with Si-H groups ( Scheme 6 ) [ 63 ]. The hydrosilylation of this polymer with triethoxysilane followed by the P-R reaction with phenyldimethylsilane produced a highly branched polymer.…”
Section: Hydride Transfer From Si To C: Piers–rubinsztajn Reaction Le...mentioning
confidence: 99%
“…This reaction yields oligodimethylsiloxanes terminated by the hydrodimethylsilyloxy groups, HSiMe This metathesis is usually an undesirable reaction that needs to be minimized, as it not only lowers the efficiency of the P-R process but also affects the structural control of the final product [95,96,102,148]. The structure of the reactants and the reaction conditions must influence the competition of the metathesis with the P-R reaction because, in many cases, the metathesis is eliminated and the P-R reaction enables a high level of the structural control of its products [22,47,63,65,77,78,97]. Kinetic studies have shown that isopropoxysilane reacted about a hundred times faster in P-R reactions than in the metathesis, but in many cases, the role of the metathesis in P-R reactions is significant [37].…”
Section: Hydride Transfer From Si To Simentioning
confidence: 99%
“…Few examples of branched siloxanes have been published so far. 19 Furthermore, in spite of the fact that numerous metallodendrimers have been reported, only very few studies have addressed the synthesis of dendronized polymers containing metallic moieties. 20…”
Section: Introductionmentioning
confidence: 99%